Design and Simulation of a Cylinder Head Structure for A Compressed Natural Gas Direct Injection Engine - A., Shamsudeen; S., Abdullah; A. K., Ariffin; Yusoff, Ali (Universiti Malaysia Pahang, 2013)
In this work, the design and simulation of four strokes, spark ignition engines with compressed natural gas direct injection is studied based on finite element analysis. The design is performed using CATIA V5, and simulated using MSC.Patran. Based on simulation results, it shows that the optimum design is achieved. The maximum von Mises stress at 5400 rpm is about 39.84 MPa for single load and 56.16 MPa for assembly load. Overall, these maximum stresses are better than original model. For the displacement at 5400 rpm, the maximum value is 0.01296 mm (single load) and 0.00972 mm (assembly load) with a decrease for about 3.55% compared to the original model. Both maximum stresses and displacement are not exceeding the material strength in order to avoid any components failure during engine operation. The result can be used to assess the quality of the design i.e. no yielding and structural failure under firing load case, can be satisfied.